Implementasi Membaca Aksara Melayu (Doa) Dalam Meningkatkan Semangat Belajar Siswa di Anuban Islam Songkhla School Thailand - Melni Kurnia; Selamat Pohan (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to determine the implementation of reading the Malay script (prayers) in increasing student enthusiasm for learning at Anuban Islam Songkhla School Thailand. This research uses a descriptive method with a qualitative approach which is carried out through field research. The research data was obtained from various relevant sources, including primary data sources and secondary data sources. In data collection, researchers conducted semi-structured interviews and made observations at Anuban Islam Songkhla School. The data obtained will be reduced, presented and concluded. The results of this study indicate that at Anuban Islam Songkhla School Thailand, the method used to increase student enthusiasm for learning is by reading the Malay script (prayer). The aim is to instill optimism in students based on the Koran. As an Islamic school, Anuban Islam Songkhla School believes that activities that involve the presence of Allah SWT will create convenience in the learning process, one of which is increasing student enthusiasm and keeping them consistent so that boredom does not arise which makes them lose their focus on learning. So the implementation of Anuban Islam School in increasing students' enthusiasm for learning is by asking students to read the Malay script (prayer) as a step that believes that students' enthusiasm can be influenced by prayer.